Mexico Financial Sector Assessment Program : SME Finance - World Bank Group; International Monetary Fund (World Bank, Washington, DC, 2017)
Major reforms and public sector efforts in recent years have focused on improving conditions for increased private sector financing. However, and despite numerous financial institutions operating in the market, financial services penetration remains low. While much progress has been made, challenges remain in terms of affordability and ease of access to finance. Banks are a major source of funding to the private sector and small and medium enterprise (SMEs) in particular, with highly standardized credit products. Other Financial Institutions (OFIs) face a number of growth and market development challenges to effectively serve the lower end of the SME segment, including funding difficulties and institutional capacity. The government plays a critical role through the development banks in promoting credit to SMEs through guarantees and second tier finance programs. The legal framework for immovable collateral (real estate) is affected by high origination costs and lengthy enforcement procedures. The legal framework for movable collateral (equipment, inventory, accounts receivables, and cash) has been modernized. Challenges remain to unify the legal framework and address enforcement delays.